Pediatric and adult high-grade glioma stem cell culture models are permissive to lytic infection with parvovirus H-1 - Josupeit, Rafael; Herold-Mende, Christel; Witt, Olaf; Lacroix, Jeannine (Viruses, 2016)
Combining virus-induced cytotoxic and immunotherapeutic effects, oncolytic virotherapy represents a promising therapeutic approach for high-grade glioma (HGG). A clinical trial has recently provided evidence for the clinical safety of the oncolytic parvovirus H-1 (H-1PV) in adult glioblastoma relapse patients. The present study assesses the efficacy of H-1PV in eliminating HGG initiating cells. H-1PV was able to enter and to transduce all HGG neurosphere culture models (n = 6), including cultures derived from adult glioblastoma, pediatric glioblastoma, and diffuse intrinsic pontine glioma. Cytotoxic effects induced by the virus have been observed in all HGG neurospheres at half maximal inhibitory concentration (IC50) doses of input virus between 1 and 10 plaque forming units per cell. H-1PV infection at this dose range was able to prevent tumorigenicity of NCH421k glioblastoma multiforme (GBM) “stem-like” cells in NOD/SCID mice. Interestingly NCH421R, an isogenic subclone with equal capacity of xenograft formation, but resistant to H-1PV infection could be isolated from the parental NCH421k culture. To reveal changes in gene expression associated with H-1PV resistance we performed a comparative gene expression analysis in these subclones. Several dysregulated genes encoding receptor proteins, endocytosis factors or regulators innate antiviral responses were identified and represent intriguing candidates for to further study molecular mechanisms of H-1PV resistance.
Gesehen am 17.09.2019